Features of business communication in international economic relations - Novik, Iryna; Chyrvon, Anna (Національний технічний університет "Харківський політехнічний інститут", 2025)
The article analyzes business communication in international economic relations with an overview of globalization, integration and digital transformations that rethink interpersonal interaction in the business environment. The main scientific concepts of the term "business communication" are considered, distinguishing behavioral, process and system approaches. The most relevant for today is the process approach, which treats communication as a continuous dynamic process that includes purposeful interaction of partners and is accompanied by the exchange of information, emotions, motivations, common meanings and expectations. This paradigm allows us to respond more adequately to changing external conditions, business needs, socio-cultural features and individual characteristics of interaction participants. Four key features of business communication in the international space are identified: its intercultural nature, formalization, purposefulness, orientation towards achieving mutual benefit and compliance with ethical and corporate standards. Special attention is paid to the challenges of the digital age, which are rethinking the content and format of business communication. The main directions for further research aimed at studying transformations in the field of business communication under the influence of global changes, digital innovations and new models of social interaction are identified. У статті проаналізовано ділове спілкування в міжнародних економічних відносинах з оглядом глобалізаційних, інтеграційних і цифрових перетворень, які переосмислюють міжособистісну взаємодію в бізнес-середовищі. Розглянуто основні наукові концепції терміна "ділове спілкування", виокремлюючи поведінковий, процесний і системний підходи. Найбільш релевантним для сьогодення визнано процесний підхід, який трактує комунікацію як безперервний динамічний процес, що містить цілеспрямовану взаємодію партнерів і супроводжується обміном інформації, емоцій, мотивацій, спільних сенсів і сподівань. Ця парадигма дозволяє адекватніше реагувати на мінливі зовнішні умови, бізнеспотреби, соціокультурні особливості і індивідуальні характеристики учасників взаємодії. Визначено чотири ключові ознаки ділового спілкування у міжнародному просторі: його міжкультурна природа, формалізованість, цілеспрямованість, орієнтація на досягнення спільної вигоди та дотримання етичних і корпоративних стандартів. Окрему увагу приділено викликам цифрової епохи, які переосмислюють зміст і формат ділової комунікації. Виявлено головні напрями для подальших досліджень, спрямованих на вивчення перетворень у сфері ділової комунікації під впливом глобальних змін, цифрових інновацій та нових моделей соціальної взаємодії.
Особливості ділового спілкування у міжнародних економічних відносинах
Keywords: business communication; economic relations; globalization; intercultural communication; foreign economic activity; ділове спілкування; економічні відносини; глобалізація; міжкультурна комунікація; зовнішньоекономічна діяльність